TUMBUHAN BERKHASIAT OBAT YANG DIMANFAATKAN SUKU MOOR DI PULAU RATEWI, KAMPUNG ARUI, DISTRIK NAPAN - WEINAMI KABUPATEN NABIRE - M. J. Sadsoeitoeboen (FMIPA Universitas Papua, 2010)
Arui are a small village, located on the island Ratewi, the District of Napan - Weinami, Nabire, Papua. Residents, who live in the village Arui, mostly are from the Moor tribes who have a myriad of knowledge about the use of herbs in everyday life, especially as a medicine. Therefore, it is necessary to do a research in order to find out the number of plant species used as a medicine, the manner of exploitation and how the usage of plants, whether singly or in combination, by the Moor tribe in the district of Napan Weinami. This research was carried out using a descriptive method with survey techniques and structured interviews. The results indicated that the Moor tribe inhabiting Arui village, utilizing 39 plants species belonging to 30 families, as medicinal materials. The most widely used is the leaves.